Analisis Alternatif Kelongsoran Bendungan Ameroro Pada Batuan Sekis Dengan Metode Elemen Hingga - Setiawan, Herdy; Rendy Satrya, Trihanyndio (Jurnal Manajemen Teknologi & Teknik Sipil, 2024)
The geological characteristics of Ameroro Dam,  dominated by schist metamorphic rocks, make this highly vulnerable to weathering, leading to reduced material strength and slope stability. This is exacerbated by rain infiltration which increases pore water pressure and earthquake loads which can trigger soil mass movement, causing a decrease in the slope safety factor.This study aims to evaluate the effect of a combination of environmental factors on slope stability using the finite element method. The research utilizes Plaxis 2D software to simulate various slope conditions under different scenarios, including static conditions, rain infiltration, and seismic loads. The results indicate that Under static conditions, the SF was 2.204, which decreased to 1.867 after rain infiltration, highlighting the adverse impact of water infiltration. To address these challenges, different reinforcement strategies were evaluated. The most effective solution was found to be the combination of 20 cm thick shotcrete, retaining wall, and 5-meter anchor, which increased the SF to 1.81, even under rain infiltration conditions. This combination enhances slope stability by providing surface protection, lateral support, and deep anchorage, effectively distributing loads and minimizing deformation risks. The findings can be the basis for developing optimized slope reinforcement strategies for dams with complex geological conditions.The geological characteristics of Ameroro Dam,  dominated by schist metamorphic rocks, make this highly vulnerable to weathering, leading to reduced material strength and slope stability. This is exacerbated by rain infiltration which increases pore water pressure and earthquake loads which can trigger soil mass movement, causing a decrease in the slope safety factor.This study aims to evaluate the effect of a combination of environmental factors on slope stability using the finite element method. The research utilizes Plaxis 2D software to simulate various slope conditions under different scenarios, including static conditions, rain infiltration, and seismic loads. The results indicate that Under static conditions, the SF was 2.204, which decreased to 1.867 after rain infiltration, highlighting the adverse impact of water infiltration. To address these challenges, different reinforcement strategies were evaluated. The most effective solution was found to be the combination of 20 cm thick shotcrete, retaining wall, and 5-meter anchor, which increased the SF to 1.81, even under rain infiltration conditions. This combination enhances slope stability by providing surface protection, lateral support, and deep anchorage, effectively distributing loads and minimizing deformation risks. The findings can be the basis for developing optimized slope reinforcement strategies for dams with complex geological conditions.